(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: The clinical and morphological picture of diabetic microangiopathy is rather specific. Diabetic retinal ischemia can lead to irreversible damage to retinal neural elements and choroidal capillaries. Diabetic nephropathy can lead to progressive renal dysfunction and chronic renal failure. Choroidal and retinal capillaries are structurally and functionally similar to those of the intestinal mucosa and renal tissue. Purpose: To assess vascular ultrastructural changes in the choroid, retina, and renal glomerular and tubular system in a rat model of pyelonephritis in the presence of type 2 diabetes mellitus. Material and Methods: Samples were obtained from 95 Wistar rats divided into three groups: group 1 (or control group) of 30 intact animals; group 2 of 15 animals with type 2 diabetes mellitus induced by intraperitoneal streptozotocin 15.0 mg/kg for 5 consecutive days; and group 3 of 50 animals with acute pyelonephritis in the presence of type 2 diabetes mellitus (streptozotocin 35.0 mg/kg on 2 days spaced by a week). Acute pyelonephritis was induced by Escherichia coli administration (107 CFU/kg) rectally. The ultrastructure of rat choroidal, retinal and renal glomerular-and-tubular vessels was examined with electron microscopy (PEM-100-01 electron microscope). Results: In rats with induced type 2 diabetes mellitus, the most significant ocular vascular changes and renal vascular changes were found in endothelial cells. These changes included findings of vacuolar degeneration in some epithelial cells, basal membrane thickening and focal necrosis of individual epithelial cells. Vessel lumens appeared focally narrowed or expanded, with red blood cells forming clumps or sludge in lumens. Some capillaries were obliterated. These changes obviously caused secondary changes in the surrounding structures. Common ocular changes included focal destruction in retinal pigment epithelium cells, destruction of retinal photoreceptor inner segments and choroidal stromal edema. Common renal changes included destruction of the podocytes of the glomerular capillary network and homogenization of the basal membrane. Vascular ultrastructural changes in the renal glomerular system were more marked in rats with experimental type 2 diabetes mellitus and pyelonephritis than in those with type 2 diabetes mellitus only. Conclusion: Electron microscopy micrographs demonstrated the ultrastructural changes in the retinal and uveal vascular systems which were of a similar type to those in the renal glomerular-and-tubular system in rats with experimental pyelonephritis in the presence of type 2 diabetes mellitus.